2023
DOI: 10.3390/ijms241914810
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor (BDNF) as a Predictor of Treatment Response in Major Depressive Disorder (MDD): A Systematic Review

Mario Ignacio Zelada,
Verónica Garrido,
Andrés Liberona
et al.

Abstract: Brain-derived neurotrophic factor (BDNF) has been studied as a biomarker of major depressive disorder (MDD). Besides diagnostic biomarkers, clinically useful biomarkers can inform response to treatment. We aimed to review all studies that sought to relate BDNF baseline levels, or BDNF polymorphisms, with response to treatment in MDD. In order to achieve this, we performed a systematic review of studies that explored the relation of BDNF with both pharmacological and non-pharmacological treatment. Finally, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Treatment with compound 46 obviously reduced the levels of pro-apoptotic proteins caspase-3 and caspase-9 in a dose-dependent manner. Furthermore, brain-derived neurotrophic factor (BDNF) has been proposed as a potential major depressive disorder biomarker. Compared with the model group, administration of compound 46 (6, 12, and 24 mg/kg) resulted in a significant increase in the expression of BDNF, and they were similar to the positive drug (fluoxetine, 12 mg/kg). Combining these results, it was clearly indicated that treatment with compound 46 can efficiently downregulate neuronal apoptosis to maintain the normal state of the hippocampal neural circuit in CUMS mice.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with compound 46 obviously reduced the levels of pro-apoptotic proteins caspase-3 and caspase-9 in a dose-dependent manner. Furthermore, brain-derived neurotrophic factor (BDNF) has been proposed as a potential major depressive disorder biomarker. Compared with the model group, administration of compound 46 (6, 12, and 24 mg/kg) resulted in a significant increase in the expression of BDNF, and they were similar to the positive drug (fluoxetine, 12 mg/kg). Combining these results, it was clearly indicated that treatment with compound 46 can efficiently downregulate neuronal apoptosis to maintain the normal state of the hippocampal neural circuit in CUMS mice.…”
Section: Resultsmentioning
confidence: 99%
“…The crucial role of hippocampal BDNF in mood regulation has been amply documented [18][19][20][21][22]. Thus, it has been confirmed that dysregulation or impairment in BDNF could precipitate MDD 3 [23] [24].…”
Section: Neurotrophic Factors and Mddmentioning
confidence: 94%
“…The differences in serum brain-derived neurotrophic factor (BDNF) levels during pharmacotherapy in major depressive disorder (MDD) patients, particularly between treatmentresponse and treatment-nonresponse groups, remain unclear [155][156][157]. Yoshimura et al studied changes in serum BDNF concentrations in first-episode, drug-naive MDD patients during antidepressant treatment and compared them to treatment-response and treatmentnonresponsive groups [88].…”
Section: Mental Health and Disorders: Breaking Barriers And Unveiling...mentioning
confidence: 99%